Development of Ready-to-Cook (Rtc) Hilsa (Tenualosa Ilisha) Curry Under Vacuum and Modified Atmosphere Packaging During Refrigerated Storage - Islam, MT; Sultana, R; Rahim, MA; Hasan, MM; Flowra, FA; Bashar, MA; Mahmud, Y (Journal of Bio-Science, 2021)
The aim of the study was to evaluate quality of ready-to-cook (RTC) hilsa curry under not sealed pack as control, vacuum as T1, MAP-1 (50% CO2 & 50% N2) as T2, and MAP-2 (40% CO2 , 30 N2 & 30% O2) pack as T3 during storage at 4±1°C. For this purpose, pH, total volatile base nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS) and aerobic plate count (APC) of three samples from each treatment were analyzed at four days interval during 28 days of storage. The pH and TVB-N values of RTC hilsa curry were within the standard limit in all samples during the storage period. However, significantly (p <0.05) lower values were observed on and after the 12th day for pH and 16th day for TVBN in all samples compared to the control. TBARS gradually increased from the 4th day for all samples except vacuum packaged sample. However, significantly (p <0.05) lower TBARS were observed in the vacuum and MAP-1 samples on and after the 8th day of storage compared to the control and MAP-2 samples. APCs gradually increased from the initial value of 5.25 log CFU/g with time in all samples. However, significantly (p <0.05) lower APCs were observed on and after the 16th day of storage in all samples compared to the control sample. The APCs exceeded the 7 log CFU/g, which is considered as the upper acceptable limit on approximately 16th day for the control, 24th day for vacuum, 22nd day for MAP-1, and 20th day for MAP-2 sample. Therefore, the vacuum packaging demonstrated the better results, which the superstores can utilize conveniently to display RTC hilsa curry with prolonged shelf life. J. Bio-Sci. 29(2): 71-79, 2021 (December)